2009
DOI: 10.1007/s11284-008-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risks in anthropogenic disturbance of nitrogen cycles in natural terrestrial ecosystems

Abstract: Anthropogenic addition of reactive nitrogen (Nr) to the biosphere is increasing globally and some terrestrial ecosystems are suffering from a state of excess Nr for biological nitrogen (N) demand, termed N saturation. Here, we review the ecological risks in relation to N saturation and prospective responses to N saturation. Excess Nr increases the risks of local extinction of rare plant species, encouragement of exotic plant species, disturbance of nutrient balance in plant organs, and increase of herbivory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 103 publications
(150 reference statements)
0
17
0
1
Order By: Relevance
“…The rapid growth since 1970 was largely driven by the emergence of a domestic N fertilizer industry and the intensive agriculture during the 1970s, and as a result, chemical fertilizer of 29 Tg N accounted for over one-half of Nr use in 2010. To a large extent, the impact of humans on the N cycle stems from their attempt to alleviate N deficiencies in agriculture by the application of fertilizer (7). Recently, the average N fertilizer application rate on Chinese cropland has reached 240 kg/ha per year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid growth since 1970 was largely driven by the emergence of a domestic N fertilizer industry and the intensive agriculture during the 1970s, and as a result, chemical fertilizer of 29 Tg N accounted for over one-half of Nr use in 2010. To a large extent, the impact of humans on the N cycle stems from their attempt to alleviate N deficiencies in agriculture by the application of fertilizer (7). Recently, the average N fertilizer application rate on Chinese cropland has reached 240 kg/ha per year.…”
Section: Resultsmentioning
confidence: 99%
“…Nr accumulation in different reservoirs has a wide variety of consequences, magnified with time as Nr moves along its biogeochemical pathways (6). These consequences result in a cascade of environmental changes, including smog, acid rain, forest dieback, coastal dead zones, biodiversity loss, stratospheric ozone depletion, and an enhanced greenhouse effect as well as health problems (5)(6)(7)(8). Currently, there is great interest in improving the efficiency of Nr use and balancing food production, energy consumption, and industrial needs with the aim of minimizing damages to environmental systems (9).…”
mentioning
confidence: 99%
“…It has been reported that increasing N availability by N deposition has outweighed soil acidification caused by acid rain in some European (Emmett et al 1998) and North American forests, but little is known about Asian forests (Fujimaki et al 2009). Also, acidification impacts are not immediate, and it may be possible that increased N availability may not necessarily offset acidification impacts in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the rapid loss of the original mineral P should cause a shortage of bioavailable P for montane ecosystems in the short-term, compared with the relatively flat region Syers 1976, Vitousek et al, 2010;Eger et al, 2011;Vincent et al, 2013). On the other hand, N deposition has dramatically increased in terrestrial ecosystems (Pardo et al, 2011;Fujimaki et al, 2009), which might decrease microbial biomass (Treseder, 2008) and change litter decomposition (Knorr et al, 2005). The P in microbial biomass was regarded as the major P pool (Turner et al, 2013), while the litter decomposition was an important avenue for P return (Fillippelli, 2008).…”
Section: Was P Lost During the 120 Years Of Pedogenesis?mentioning
confidence: 99%